Kritik Terhadap Struktur Kekuasaan dalam Pendidikan Islam Di Sekolah MI Hajar Abyadl - Kalsum, Umi; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
The power structure in Islamic education at MI Hajar Abyadl plays an important role in influencing teachers' involvement in educational decision-making. The focus of this research is to understand the power structure in MI Hajar Abyadl and identify power practices that are considered unfair or discriminatory. The research method used is a qualitative approach with semi-structured interview techniques. The research findings reveal that the power structure in MI Hajar Abyadl is organized in a clear hierarchy, with the school principal at the center of decision-making and teachers playing a role in implementing these policies. However, there are several discrepancies in the policy implementation that may impact educational fairness. One example is the exercise of power deemed unfair or discriminatory, such as differences in access to facilities and learning opportunities between students from wealthy and less privileged families. This can lead to inequality, hindering students' potential development. On the other hand, while there are indications of discriminatory practices, the existing policies are insufficient to address these imbalances comprehensively. As a solution, it is necessary to evaluate the current structure and policies to create a more equitable education system for all students.